SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN KOMPUTER DENGAN METODE BROWN GIBSON - I Made Aditya Virgiawan (LPPM Universitas Dhyana Pura, 2015)
Decision Support System is an interactive system that supports decision in the decision- making process through the alternatives - alternatives obtained from the processing of data, information and design models. The results provided by the system as a decision support can provide alternative solutions to problems for users by providing a range of possible results in accordance with the conditions of the problem parameters that can be changed.Creating a Decision Support System online, using the method of Brown Gibson, is able to resolve the issue of election for selecting computer, the steps of this method are simple, easy to understand, effective and efficient. Brown Gibson methods chosen because each computer has a different character or condition, in estab- further discussion will be referred to as factors. These factors will affect the calculation to re-determine the computers that will be selected. With the web-based decision support system will be the technology that not only provides convenience, butis able provide solutions to someone in the right laptop mememilih and also suits your needs and budget .Procedures and steps that must be taken to apply the method of Brown Gibson in this study can be described as follows: (1) elimination of any alternative site on the face of the computer that is clearly not feasible and feasible to be chosen, for example the price of computers that exceed the budget. (2) Calculate and set performance measurement of ob-yektif factor (OFI) for each alternative. With the web-based decision support system is going to be a technology that not only provides convenience, but is able to provide a solution to someone in choosing the right computer and also according to the needs and budgets.Keywords : System, Decision Support, Brown Gibson